2016
DOI: 10.1111/ijfs.13209
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of gaseous chlorine dioxide against Salmonella enterica Typhimurium on grape tomato (Lycopersicon esculentum)

Abstract: Summary The aim of this study was to investigate the effects of gas level and treatment condition on antimicrobial efficacy of ClO2 gas against Salmonella enterica Typhimurium on grape tomato (Lycopersicon esculentum). Grape tomatoes were dip‐inoculated with inoculum of S. enterica Typhimurium TISTR 292 (ATCC 13311) (9.79 ± 0.39 log CFU mL−1) and allowed to dry before treatments. The pre‐inoculated samples were exposed to 0.15–0.85 mg of ClO2 gas, for up to 58 min. The treatments at 4 and 25 °C resulted in pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Several studies have investigated the disinfection of tomatoes using ClO 2 ( Praeger et al, 2018 ; Sun et al, 2019 ). For artificially inoculated human pathogens, 5–7 log reduction in microbial load has been observed with gaseous ClO 2 concentrations < 1 ppm ( Bhagat et al, 2010 ; Olanya et al, 2015 ; Netramai et al, 2016 ). For instance, a 12 min exposure to 0.5 ppm ClO 2 resulted in >5 log reduction in Salmonella and L. monocytogenes loads in hydroponically grown tomatoes ( Bhagat et al, 2010 ).…”
Section: Effects Of Chlorine Dioxide Treatment On Microbes Affecting Fresh Producementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the disinfection of tomatoes using ClO 2 ( Praeger et al, 2018 ; Sun et al, 2019 ). For artificially inoculated human pathogens, 5–7 log reduction in microbial load has been observed with gaseous ClO 2 concentrations < 1 ppm ( Bhagat et al, 2010 ; Olanya et al, 2015 ; Netramai et al, 2016 ). For instance, a 12 min exposure to 0.5 ppm ClO 2 resulted in >5 log reduction in Salmonella and L. monocytogenes loads in hydroponically grown tomatoes ( Bhagat et al, 2010 ).…”
Section: Effects Of Chlorine Dioxide Treatment On Microbes Affecting Fresh Producementioning
confidence: 99%
“…For instance, a 12 min exposure to 0.5 ppm ClO 2 resulted in >5 log reduction in Salmonella and L. monocytogenes loads in hydroponically grown tomatoes ( Bhagat et al, 2010 ). With an increased exposure time (approximately 1 h), grape tomatoes exhibited >7 log reduction in the load of Salmonella spp., at 25°C ( Netramai et al, 2016 ). Trinetta et al (2010) evaluated the efficacy of short-term exposure of high ClO 2 concentrations in the inactivation of S. enterica inoculated on tomatoes and observed that the initial populations (6 log) were reduced to 3 log, 2 log, and 1 log in response to 8 ppm ClO 2 for 60 s, 10 ppm ClO 2 for 120 s, and 10 ppm for 180 s, respectively.…”
Section: Effects Of Chlorine Dioxide Treatment On Microbes Affecting Fresh Producementioning
confidence: 99%
“…Hydrochloric acids (Netramai et al., 2016; Simonet & Gantzer, 2006), sulfuric acids (H. Lee et al., 2018), phosphoric acids (Rodgers et al., 2004), and citric acids (Kingsley et al., 2018; Young & Setlow, 2003) have all been used to generate hydrogen ions. However, volatility, byproducts, and generation rate are the major concerns for these activators.…”
Section: Methods To Generate Gaseous Chlorine Dioxidementioning
confidence: 99%
“…Schematic diagrams of different gaseous ClO 2 treatment systems: (A) gaseous ClO 2 cabinet with fan (S.‐Y. Lee et al., 2006); (B) climatic chamber with ClO 2 packaging film (Netramai et al., 2016); (C) gaseous ClO 2 chamber with injection port and ClO 2 reservoir (Zhang et al., 2019); and (D) test chamber for ClO 2 inactivation (S.‐H. Park & Kang, 2015).…”
Section: Methods To Generate Gaseous Chlorine Dioxidementioning
confidence: 99%
See 1 more Smart Citation